Effect of ketoconazole on isolated mitochondria from Candida albicans. - Shigematsu, M L (1982)
Ketoconazole, an oral antimycotic imidazole drug, blocked the transport of electrons in the respiratory chain of Candida albicans under aerobic conditions with different substrates, such as NADH and succinate. This effect was a nonspecific inhibition of NADH oxidases and succinate oxidases. The addition of ketoconazole to C. albicans mitochondria without a substrate resulted in strong reduction of cytochrome a3, as revealed by difference spectra (reduced versus oxidized). This indicated that there was a specific interaction between ketoconazole and cytochrome c oxidase. A spectrophotometric analysis confirmed that the cytochrome oxidases other than cytochrome c oxidase were not inhibited because subsequent addition of any substrate caused an increased level of reduction of all of the other respiratory chain components compared with the control. Consequently, our data strongly suggested that the primary site of ketoconazole inhibition on isolated mitochondria from C. albicans is the most distal portion of the respiratory chain.